2015
DOI: 10.1007/s00586-015-4229-y
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular metal spacers as standalone or with pedicle screw augmentation, in posterior lumbar interbody fusion: a prospective, randomized controlled trial

Abstract: In this study, TM spacers were found to provide a solid construct at more than 6-year follow-up after PLIF for DDD both with and without additional pedicle fixation. The clinical, but also radiological results were not significantly different between both cohorts. Future studies focusing on the differences of SA and PF at L4/5 level should be powered to study differences in post-surgery stability at the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
(65 reference statements)
2
13
0
Order By: Relevance
“…Similar clinical evaluation results including Oswestry Disability Index (ODI), VAS and SF-36 scores were revealed at 2-year follow-up point [134]. And equivalent X-ray results of both groups evaluated at 6-year follow-up proposed that porous Ta standalone fashion could provide stability for lumbar spine interbody fusion without additional fixation or bone grafting [134]. However, RCTs are still rare used to definitely corroborate the clinical value of porous Ta cages for lumbar spine fusion surgery either used as standalone fashion or augmented with posterior screws.…”
Section: Spine Intervertebral Fusionsupporting
confidence: 66%
See 2 more Smart Citations
“…Similar clinical evaluation results including Oswestry Disability Index (ODI), VAS and SF-36 scores were revealed at 2-year follow-up point [134]. And equivalent X-ray results of both groups evaluated at 6-year follow-up proposed that porous Ta standalone fashion could provide stability for lumbar spine interbody fusion without additional fixation or bone grafting [134]. However, RCTs are still rare used to definitely corroborate the clinical value of porous Ta cages for lumbar spine fusion surgery either used as standalone fashion or augmented with posterior screws.…”
Section: Spine Intervertebral Fusionsupporting
confidence: 66%
“…Furthermore, in a randomized controlled trail (RCT), 80 patients were either enrolled into standalone porous Ta cage fusion group or pedicle screws supplemented group [134]. Similar clinical evaluation results including Oswestry Disability Index (ODI), VAS and SF-36 scores were revealed at 2-year follow-up point [134].…”
Section: Spine Intervertebral Fusionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, observation of the interbody space is sometimes difficult due to halation created by metals, such as tantalum, contained in cages. 9 In this study, therefore, instead of arthrodesis we used VECF as our primary outcome. The assessment of VECF is easier than that of arthrodesis and is expected to decrease bias in observers' judgments.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that titanium porous surface EBMT, prepared based on superior biological properties, can promote cell attachment, growth, and stem cell osteogenic differentiation. [ 20 22 ] Biological materials can increase the metal-binding capacity of cells, thus greatly increasing bone prosthesis metal-binding capacity, which results in better mechanical properties. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%